On the vital areas of intrusion detection systems in wireless sensor networks - Abduvaliyev, Abror; Pathan, Al-Sakib Khan; Jianying, Zhou; Roman, Rodrigo; Wai-Choong, Wong (IEEE, USA, 2012)
This paper surveys recently proposed works on Intrusion Detection Systems (IDS) in WSNs, and presents a comprehensive classification of various IDS approaches according to their employed detection techniques. The three main categories explored in this paper are anomaly detection, misuse detection, and specification-based detection protocols. We give a description of existing security attacks in WSNs and the corresponding proposed IDS protocols to tackle those attacks. We analyze the works with respect to the network structure of WSNs. In addition, we highlight various critical shortcomings that IDSs currently have and define future research tracks for IDSs in wireless sensor networks. Though a few restricted survey works on this topic have already been done, we feel that there is a great need of performing a detailed and comprehensive study on the vital aspects so that the IDS in WSN could be analyzed from all the need-to-know angles. Thus, the papers main aim is to include the most recent advancements in this area as well as to predict the future course of research so that the general as well as expert readers could be greatly benefited.